Vocal complaint in physical education teachers and its association with the cardiovascular system - Cunha, Denise S. [UNESP]; Abreu, Luiz Carlos de; Frizzo, Ana Cláudia Figueiredo [UNESP]; Cardoso, Marco A. [UNESP]; Valenti, Vitor Engrácia [UNESP] (My University, 2014)
Background: We examined the vocal complaints and evaluated the correlation between the vocal handicap index (VHI) and heart rate variability (HRV) in physical education teachers. We evaluated 46 teachers. Method: The subjects were investigated regarding voice complaint and the VHI was applied. HRV was recorded at seated rest for ten minutes and it was analyzed in the time, frequency domains, geometric indices and fractal exponents. The three domains of the VHI were correlated with the indices of HRV. Results: The physical education teachers presented a VHI score much below the standard of the physiological normality. There was correlation of the organic domain of the VHI with the NN50 and pNN50 and correlation of the functional domain and organic domain of the VHI with the HF index of HRV. Conclusion: The physical education teachers evaluated reported vocal complaints that affected their function and it is suggested to be related with the cardiac autonomic regulation.